Spectrophotometric Estimation of Metformin Hydrochloride in Pharmaceutical Dosage Forms - Mathrusri Annapurna, M.; Nagoji, K.E.V.; Srinivasa Rao, S.; Patro, S.S. (Asian Journal of Chemistry, 2010)
Two sensitive and reproducible spectrophotometric methods have been developed for the estimation of metformin hydrochloride in pure and its dosage forms by using 0.1 N NaOH (method A) and pH 7.4 phosphate buffer (method B). The maximum absorbance was observed at 233 nm in both the methos. Beer's law was obeyed in the concentration of 1–30 μg/mL in method A and 1–20 μg/mL in method B.